New indications and platforms for CAR‐T therapy in lymphomas beyond DLBCL - Madiha Iqbal; Bipin N Savani; Mehdi Hamadani (eJHaem, 2022)
Abstract CD19‐directed chimeric antigen receptor T‐cell therapy (CAR‐T) represents a significant advancement for patients with relapsed/refractory large B‐cell lymphoma (LBCL). Long‐term follow‐up confirms durable remissions in nearly half of the patients, a population that was previously estimated to have a median survival of around 6 months with standard salvage therapy. This initial success of CAR‐T has led to significant expansion across other lymphoma histologies resulting in the recent regulatory approval of CAR‐T in mantle cell lymphoma and follicular lymphoma. Additionally, multiple novel platforms of CAR‐T therapy are under development to improve efficacy and limit toxicity such dual antigen targeting, allogeneic and natural killer CARs. In this review, we focus on the new indications of CAR‐T in lymphomas beyond LBCL as well as emerging platforms of CAR‐T therapy.